2021
DOI: 10.3389/falgy.2021.718267
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of Steroid-Unresponsive Severe Asthma

Abstract: Asthma is a heterogeneous respiratory disease characterized by airflow obstruction, bronchial hyperresponsiveness and airway inflammation. Approximately 10% of asthma patients suffer from uncontrolled severe asthma (SA). A major difference between patients with SA from those with mild-to-moderate asthma is the resistance to common glucocorticoid treatments. Thus, steroid-unresponsive uncontrolled asthma is a hallmark of SA. An impediment in the development of new therapies for SA is a limited understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 92 publications
(154 reference statements)
0
9
0
Order By: Relevance
“…Several mechanisms may exist for steroid resistance, and these may differ in patients who are non-responsive to corticosteroid treatment [151]. Increased expression of the non-responsive beta isoform of glucocorticoid receptor, activation of p38 MAPK leading to phosphorylation of glucocorticoid receptors and reduced corticosteroid binding affinity within nucleus, excessive activation of the JNK pathway, reduced suppression or no effect of corticosteroid on cytokine release, impaired nuclear localization of glucocorticoid receptors, and defective histone acetylation are some of the plausible reasons for steroid-resistance [163][164][165][166]. One report has also identified that the circadian clock gene disruption corroborates with the loss of efficacy of synthetic dexamethasone [114].…”
Section: Role Of Tlr4 In Resistance To Corticosteroid Treatmentmentioning
confidence: 99%
“…Several mechanisms may exist for steroid resistance, and these may differ in patients who are non-responsive to corticosteroid treatment [151]. Increased expression of the non-responsive beta isoform of glucocorticoid receptor, activation of p38 MAPK leading to phosphorylation of glucocorticoid receptors and reduced corticosteroid binding affinity within nucleus, excessive activation of the JNK pathway, reduced suppression or no effect of corticosteroid on cytokine release, impaired nuclear localization of glucocorticoid receptors, and defective histone acetylation are some of the plausible reasons for steroid-resistance [163][164][165][166]. One report has also identified that the circadian clock gene disruption corroborates with the loss of efficacy of synthetic dexamethasone [114].…”
Section: Role Of Tlr4 In Resistance To Corticosteroid Treatmentmentioning
confidence: 99%
“…Therefore, targeted treatment options, as well as clinically applicable biomarkers, are still largely under exploration ( 92 ). In this context, the clinically relevant issue of whether “true” non-T2 asthma really exists has been raised, as high-dose ICS and oral corticosteroids (OCS) may potentially minimize blood eosinophils and FeNO levels, therefore masking preexisting T2 inflammation ( 93 ).…”
Section: Biomarkers In Non-t2 Asthmamentioning
confidence: 99%
“…Most patients require combinatorial therapy due to the presence of different immune phenotypes. 7 For instance, a study conducted on asthmatic patients by dividing them into different groups like mixed asthmatics (eosinophilic/neutrophilic), paucigranulocytic, neutrophilic with usual FEV1, and neutrophilic with less FEV1 (asthmatics with smoking are included). Macrophage counts were estimated and observed a specific incline in the interferon regulatory factor 5 (IRF5+) levels and decline in the interferon regulatory factor 10 (IRF 10) levels.…”
Section: Multiple Signaling Involved In Severe Steroid Resistant (Ssr...mentioning
confidence: 99%
“…The degree of unresponsiveness towards corticosteroid therapy in asthmatic patients is up to 10%. 7 Corticosteroids can modulate the gene expression of certain genes to minimize the pathophysiology underlying asthma; in certain cases, the prolonged usage of corticosteroids can induce variable gene expression as a result, the asthma patients attain steroid resistance. Side effects arising from corticosteroid therapy worsen the quality of life in asthma patients and cause a higher socio-economic burden for the patients receiving regular therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%